Study of dried-out pattern formation in urea-protein droplets placed on a glass substrate - Pathak B. (My University, 2025)
In the current work, we have studied the drying of two important bio colloids (protein and urea) using sessile droplets on a glass substrate. Urea denatures protein and alters the behaviour of the protein molecules. The concentration of urea plays a crucial role in determining the functioning of proteins. Therefore, various diseases can be diagnosed if there is any change in concentration of these components in the body fluids (blood and urine).We found that the concentration also alters the final dried-out morphologies in droplets of bio-colloids. The analysis of these patterns will thus assist in understanding the interaction between the molecules. The current investigation provides physical insights into the formation of these different morphologies. The findings can be further extended for the preliminary diagnosis of diseases using patterns formed of bio-fluid droplets. © 2024 Elsevier B.V.